2023
DOI: 10.3389/fmicb.2023.1150129
|View full text |Cite
|
Sign up to set email alerts
|

Egg yolk antibody combined with bismuth-based quadruple therapy in Helicobacter pylori infection rescue treatment: a single-center, randomized, controlled study

Abstract: BackgroundThe increasing antibiotic resistance is the main issue causing Helicobacter pylori (H. pylori) eradication failure. As a nutritional supplement, Egg Yolk Antibody (Ig Y) provides a new approach for H. pylori infection rescue therapy.MethodsIn this randomized, controlled study, 100 H. pylori-positive patients with previous H. pylori eradication treatment were included. All individuals received standard bismuth-containing quadruple therapy twice daily (5 mg ilaprazole, 100 mg doxycycline, 500 mg clarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…After 4 weeks from the end of the treatment, H. pylori eradication, assessed through urea breath tests and the Global Overall Symptom Scale (GOS), indicated that both the case and control groups achieved satisfactory eradication rates. However, it is noteworthy that IgY‐ H. pylori effectively reduced disease symptoms and had fewer side effects 36 …”
Section: Resultsmentioning
confidence: 99%
“…After 4 weeks from the end of the treatment, H. pylori eradication, assessed through urea breath tests and the Global Overall Symptom Scale (GOS), indicated that both the case and control groups achieved satisfactory eradication rates. However, it is noteworthy that IgY‐ H. pylori effectively reduced disease symptoms and had fewer side effects 36 …”
Section: Resultsmentioning
confidence: 99%